1999
DOI: 10.1111/j.1945-5100.1999.tb01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial ages of ordinary chondrites from the Lewis Cliff stranding area, East Antarctica

Abstract: Abstract-We determined terrestrial ages of ordinary chondrites from the Lewis Cliff stranding area, East Antarctica, on the basis of the concentrations of cosmogenic loge (ts = 1.5 1 Ma), 26A1 (ts = 0.705 Ma), and 36Cl (t% = 0.301 Ma). After an initial 26A1 pray survey of 91 meteorites suggested that many have terrestrial ages >O. 1 Ma, we selected 62 meteorites for 1OBe and 26A1 measurements by accelerator mass spectrometry (AMS) and measured 36Cl in twelve of those. Low terrestrial ages (<0.1 Ma) were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Fritz et al (2005) found a correlation among martian meteorites between high shock pressure induced during launch and short transfer time to Earth. Because the nakhlites and Chassigny appear to have been ejected from Mars in the same impact event before $11 Ma ago and because very few meteorites, even those that fell in Antarctica, are preserved for more than $1 Ma (Welten et al, 1997(Welten et al, , 1999, it is plausible that there were highly shocked nakhlites and chassignites that reached Earth millions of years ago that were lost to the geological record (Fritz et al, 2005). If this selection effect is valid, it would imply that those martian samples that reached Earth more recently tend to be among the less shocked.…”
Section: Nakhlitesmentioning
confidence: 98%
“…Fritz et al (2005) found a correlation among martian meteorites between high shock pressure induced during launch and short transfer time to Earth. Because the nakhlites and Chassigny appear to have been ejected from Mars in the same impact event before $11 Ma ago and because very few meteorites, even those that fell in Antarctica, are preserved for more than $1 Ma (Welten et al, 1997(Welten et al, , 1999, it is plausible that there were highly shocked nakhlites and chassignites that reached Earth millions of years ago that were lost to the geological record (Fritz et al, 2005). If this selection effect is valid, it would imply that those martian samples that reached Earth more recently tend to be among the less shocked.…”
Section: Nakhlitesmentioning
confidence: 98%
“…In Antarctica, weathering is very slow with some meteorites surviving more than 2 Ma. [31] In hot desert environments, most meteorites have terrestrial ages of a few 10'000 years. [32] Metal is completely weathered within less than 20'000 years while troilite is more resistant but generally completely weathered in the oldest meteorites with terrestrial ages >30'000 years.…”
Section: Weathering Of Meteoritesmentioning
confidence: 99%
“…See text for details. meteorites are less than 1 Ma (Welten et al 1997;Welten et al 1999). Given the limited preservation of meteorites on Earth, the lack of highly shocked nakhlites may be due to the fact that they were transferred to Earth substantially faster than the weakly shocked ones, and, therefore, are less likely to be preserved over a given time.…”
Section: Sub-groupmentioning
confidence: 99%
“…Assuming that the survival time of meteorites on the surface of Earth is limited to about 1 Ma (Welten et al 1997(Welten et al , 1999, Armstrong et al (2002) evaluated the likelihood for preservation of ejected fragments from the terrestrial planets on the surface of the Moon. They concluded that on the lunar surface samples from terrestrial planets originating from the time of the early heavy bombardment 3.9 Ga ago may be found.…”
Section: Interplanetary Transfer Of Solid Mattermentioning
confidence: 99%